LOW PLATELETCRIT IS ASSOCIATED WITH REDUCED PROGRESSION – FREE AND OVERALL SURVIVAL IN CHRONIC LYMPHOCYTIC LEUKEMIA: Plateletcrit and Chronic Lymphocytic Leukemia - Ozbalci, Demircan; Alanoglu, Emine Guchan; Findos, Eda; Eroglu, Hande Nur (Journal of Medical Biochemistry, 2022)
BACKGROUDAlterations of plateletcrit and mean platelet volume (MPV) and pathogenesis of chronic lymphocytic leukemia (CLL) have been linked to various inflammatory disorders. The prognostic impact of plateletcrit and MPV were evaluated.METHODS                MPV and plateletcrit levels of both CLL and control group were compared and then in CLL patients, additional diseases, leukocyte count, platelet count, lactate dehydrogenase, Rai stage, progression-free and overall survival, mutations, if any, and chemotherapy, if any, were recorded. Then, the relationship between MPV and plateletcrit values and these parameters were evaluated in CLL patients.RESULTS                Platelet and plateletcrit values ​​were found to be significantly lower in CLL patients than the control group (p
Keywords: Plateletcrit; chronic lymphocytic leukemia; prognosis; overall survival